Vacuolar ATPase as a potential therapeutic target and mediator of treatment resistance in cancer - Bradleigh Whitton; Haruko Okamoto; Graham Packham; Simon J. Crabb (Cancer Medicine)
Abstract Vacuolar ATPase (V‐ATPase) is an ATP‐dependent H+‐transporter that pumps protons across intracellular and plasma membranes. It consists of a large multi‐subunit protein complex and influences a wide range of cellular processes. This review focuses on emerging evidence for the roles for V‐ATPase in cancer. This includes how V‐ATPase dysregulation contributes to cancer growth, metastasis, invasion and proliferation, and the potential link between V‐ATPase and the development of drug resistance.